MENINGKATKAN KEMAMPUAN MENGENAL ANGKA MELALUI MEDIA KARTU ANGKA BERGAMBAR DI TK CAHAYA MULYA PALARAN TAHUN PEMBELAJARAN 2020/2021 - Arbayah; Damayanti, Sri; Sjamsir, Hasbi (Manajemen Pendidikan Program Doktor, 2023)
Improving the Ability to Recognize Numbers through Group B Picture Number Card Media at TK Cahaya Mulya Palaran Learning Year 2020/2021 (guided by Munir, M.Si). The purpose of the study to find out whether the ability to recognize the numbers of group B students can increase through the media of picture number cards at TK Cahaya Mulya Palaran Type of Research is classroom action research (PTK). The study was carried out for 10 days, from March 25 to April 8, 2021. The subjects of the study were grade B students of Cahaya Mulya Palaran Kindergarten with a total of 16 students. The learning method through playing using picture number cards serves as an effective and fun learning model, students more easily and quickly grasp the goals and teaching materials because it is done by playing. The results showed that this method can improve the ability to recognize numbers through the media of picture number cards in group B students of Cahaya Mulya Palaran Kindergarten. End of cycle II h..